Compassionate care challenges and barriers in clinical nurses: A qualitative study - Sima Babaei; Fariba Taleghani (Wolters Kluwer Medknow Publications, 2019)
Background: Compassion is the heart of nursing care. Barriers to compassion in nursing may be influenced by the prevailing culture and religion of a society. Determining the barriers to providing compassion-based care would help nurses to plan better and more appropriate interventions. This study aimed to explore the challenges and barriers to compassionate care in nurses. Materials and Methods: This ethnographic study was performed in 2014-2016. The study participants consisted of 40 nurses, 16 patients, and 8 family members in medical and surgical wards. Data collection was performed through observations and interviews. Data analysis was performed based on Strauss and Corbin's constant comparative method. Results: Data analysis defined three themes as the challenges and barriers to compassionate care; challenges and barriers related to the contextual environment of hospitals, sociocultural challenges and barriers, and challenges; and barriers related to staff. Conclusions: This study described the challenges and barriers to compassionate care. Therefore, to eliminate these barriers and challenges, corrective action should be taken by managers. Attention to teaching the concept of compassion and patient-centered care and increasing the number of nurses and positive attitude toward the nursing profession in clinical environment can be effective in providing compassionate care.